2021
DOI: 10.3390/neurolint13030046
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Assessment of Ulnar Nerve Tension Using Shear-Wave Elastography

Abstract: Background: Ulnar nerve compression at the elbow level is the second-most common entrapment neuropathy. The aim of this study was to use shear-wave elastography for the quantification of ulnar nerve elasticity in patients after ulnar nerve decompression with anterior transposition and in the contralateral non-operative side. Method: Eleven patients with confirmed diagnosis and ulnar nerve decompression with anterior transposition were included and examinations were performed on an AixplorerTM ultrasound system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…SWE confirmed the anterior location of the ulnar nerve relative to the rotation axis of the elbow, with a decreased tension in the ulnar nerve during elbow flexion: the values of the shear elastic modulus in the ulnar nerve decreased from 107.2 to 79.1 kPa with elbow flexion. These shear elastic modulus values were comparable to those recently reported in patients before and after anterior transposition of the ulnar nerve [ 5 ]. Due to the absence of extrinsic compression factors in this anterior nerve location, excessive friction and stretching are other potential mechanisms to consider.…”
Section: Discussionsupporting
confidence: 90%
“…SWE confirmed the anterior location of the ulnar nerve relative to the rotation axis of the elbow, with a decreased tension in the ulnar nerve during elbow flexion: the values of the shear elastic modulus in the ulnar nerve decreased from 107.2 to 79.1 kPa with elbow flexion. These shear elastic modulus values were comparable to those recently reported in patients before and after anterior transposition of the ulnar nerve [ 5 ]. Due to the absence of extrinsic compression factors in this anterior nerve location, excessive friction and stretching are other potential mechanisms to consider.…”
Section: Discussionsupporting
confidence: 90%
“…The modified Downs and Black checklist score varied from 9 to 13. Five studies showed good quality (more than 11 points) [49,[52][53][54][55], and 11 showed fair quality (8-11 points) [36,37,50,[56][57][58][59][60][61][62][63]. None of the included studies scored below 9 points.…”
Section: Quality Of the Studiesmentioning
confidence: 94%
“…The characteristics of the 16 included studies are shown in Tables 2 and 3. In the upper extremity, the median nerve (MN) was assessed in six studies [36,37,55,[61][62][63], while the ulnar nerve (UN) was explored in three studies [37,57,60]. In the lower extremity, the sciatic nerve (SN) and the tibial nerve (TN) were evaluated in six studies [49,50,53,54,58,59] and four studies [36,52,54,56], respectively.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…This growing catalogue currently includes the ulnar nerve, [159] radial nerve, [160] and median nerve [161] among many others. Other studies, such as this one by Durand et al, 2021, have started comparing the elastic properties of healthy nerves against neuropathic nerves, in this case comparing entrapped ulnar nerves post decompression against the contralateral non-operative side [162].…”
Section: Shear Wave Elastography (Swe)mentioning
confidence: 99%